PENGARUH TAX AVOIDANCE RISK TERHADAP CASH HOLDING POLICY PERUSAHAAN DI INDONESIA - Hardianto, Yudi Tri; Kustiani, Nur Aisyah; Ramadhan, Muhammad Rheza (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2017)
This study aims to determine the effect of Tax Avoidance Risk to Cash Holding Company Policy in Indonesia. Tax Avoidance Risk is measured by Cash Effective Tax Rate proxy and Cash Holding Policy is measured by Cash Ratio proxy (cash and cash equivalent divided by total asset or total sales). Based on regression with random effect model on 74 samples, we found that Tax Avoidance Risk has no effect on Cash Holding Policy after controlled by market to book ratio variable, firm size, leverage, capital expenditure, volatility of cash flow, dividend, research and development , Acquisitions, cash flow after tax, and industrial sector.